Conceptual generalizations as for the content of individual socio-psychological characteristics of personality development as a leader - Moroz, M. V.; Laamanen, R. V. (НТУ "ХПІ", 2014)
The article is devoted to the problems of the leader's personality development in the context of the content of individual socio-psychological aspects of its formation. An attempt on the specification of the objects and the process of development of the individual leader and clarified the nature of the development process within the general content of the interpretation of the relevant category. There were considered several specific age periods of personal development (adolescence) in the context of their compliance with the main periods of human socialization and development of leadership qualities. The place and role of public institutes and institutions in shaping personality traits of new leader. In addition, the article contains the conclusions and generalizations about the content of individual socio-psychological characteristics of the leader's personality development.

Стаття присвячена проблематиці розвитку особистості лідера в контексті змісту окремих соціально-психологічних аспектів її формування. Здійснена спроба щодо конкретизації об’єктів та суб’єктів процесу розвитку особистості лідера, а також з’ясовано сутність процесу розвитку у межах загального змісту тлумачення відповідної категорії. Розглянуто окремі вікові періоди розвитку особистості (юнацький вік) в контексті їх відповідності основним періодам соціалізації людини та розвитку її лідерських якостей. Визначено місце та роль суспільних інститутів та інституцій у формуванні нової якості особистості лідера. Крім того, стаття містить висновки та узагальнення щодо змісту окремих соціально-психологічних особливостей розвитку особистості лідера.
Концептуальні узагальнення щодо змісту окремих соціально-психологічних особливостей розвитку особистості лідера
Keywords: socialization; institutes; institutions; human "I"; adolescence; соціалізація; вік юнацький; людське «Я»